Organism Ageing – Universal Illness or Inevitably Arising Process? - O. G. Ishonina (Медицинский вестник Юга России, 2011)
The paper presents a literature review study of aging as a process of normal or physiological and pathological age-related changes. Today there is no single perspective on the aging process, but it is clear that the basis of aging is the internal instability of biological molecules. Some authors see the relationship with aging-associated disease age. Other authors define aging as the most universal disease, and under normal aging understand the amount and intertwining of the top ten diseases generated by ontogenetic and accumulation mechanisms. It is clear that there is no disease that would have been the cause of death for all older individuals, but also distinguish the disease associated with aging (aging-dependent), and diseases associated with age (age-dependent).